The Effect Of Salary On Employee Productivity With The Mediation Of Employee Motivation And Job Satisfaction In Retail Companies In Tangerang - Susilowati, Nofi; Fadli, Jul Aidil (Jurnal Ilmiah Manajemen Kesatuan, 2023)
The development of today's business life has progressed very rapidly, especially in trade in retail companies. This can be seen from the increasing number of retail companies that have sprung up in the hope that market leaders can attract the attention of consumers, so that competition in the retail trade is getting tougher. This study aims to determine the effect of salary on employee work productivity by mediating employee motivation and job satisfaction in retail companies in Tangerang. This research was conducted on retail company employees who have worked for at least 1 year in the Tangerang area. The sampling method used purposive sampling with a total sample of 110 respondents. The number of statements given to respondents was 22 statement items. The results of this study indicate that there is a significant effect of salary on employee motivation, salary on job satisfaction, employee motivation on employee work productivity, job satisfaction on employee work productivity, salary that is not a significant effect on employee productivity, and a significant effect on work motivation employees on job satisfaction. Keywords: Salary, Employee Motivation, Job Satisfaction, Employee Productivity